Numerical and Intelligent Scenarios in Higher Vocational Education in the Era of Artificial Intelligence - Rui, Jiang (Journal of Educational Research and Policies, 2025)
This article explores the development background, models, practical challenges, and development paths of ‘numerical and intelligent scenarios’ in China’s higher vocational education in the era of artificial intelligence. With the rapid advancement of AI technology, higher vocational education is transitioning from traditional models to numerical and intelligent scenarios, innovating teaching methods through immersive experiences, differentiated education, and interactive teaching. However, challenges such as lagging infrastructure construction, uneven distribution of digital resources, slow transformation of teaching models, and insufficient depth of industry-education integration persist. In response, the article proposes development paths including strengthening infrastructure construction, optimizing digital resource allocation, promoting teaching model innovation, and deepening industry-education integration to provide theoretical references and practical guidance for the construction of numerical and intelligent scenarios in higher vocational education.